2001
DOI: 10.1080/074811801750073251
|View full text |Cite
|
Sign up to set email alerts
|

International Comparison of Studies Using the Perinatal Grief Scale: A Decade of Research on Pregnancy Loss

Abstract: The Perinatal Grief Scale (PGS) has been used in many studies of loss in pregnancy, including miscarriage, stillbirth, induced abortion, neonatal death, and relinquishment for adoption. This article describes 22 studies from 4 countries that used the PGS with a total of 2485 participants. Studies that report Cronbach's alpha for their own samples give evidence of very high internal consistency reliability. Evidence for the validity of the PGS is also reviewed, such as convergent validity seen in its associatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
114
1
10

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 143 publications
(137 citation statements)
references
References 18 publications
(28 reference statements)
12
114
1
10
Order By: Relevance
“…The mean value for PGS-33 Grief was in accord with the values reported in the literature (Toedter, Lasker, & Janssen, 2001). Although the mean value for each MFODS individual scale was within an SD of the value reported by Neimeyer and Moore (1994), the present study's participants compared with the women reported by Neimeyer and Moore (1994) had somewhat greater Fear for Significant Others, Fear of Conscious Death, and Fear of Premature Death (Table 1).…”
Section: Descriptive Statisticssupporting
confidence: 79%
“…The mean value for PGS-33 Grief was in accord with the values reported in the literature (Toedter, Lasker, & Janssen, 2001). Although the mean value for each MFODS individual scale was within an SD of the value reported by Neimeyer and Moore (1994), the present study's participants compared with the women reported by Neimeyer and Moore (1994) had somewhat greater Fear for Significant Others, Fear of Conscious Death, and Fear of Premature Death (Table 1).…”
Section: Descriptive Statisticssupporting
confidence: 79%
“…Perhaps, it was women's personal resources such as emotional strength (Swanson, 2000) or having a coping repertoire born of prior life experiences (Van & Meleis, 2003) that influenced their resolution. Likewise, the presence of environmental resources such as the presence of a caring mate and the support of friends and family (Conway & Russell, 2000;Swanson, 2000;Toedter et al) may have contributed to emotional healing.…”
Section: Discussionmentioning
confidence: 99%
“…The intensity of maternal grief was measured with the PGS-33 (Potvin et al, 1989), which is a psychometrically valid and reliable 33-item self-report questionnaire with three factor-analyzed 11-item subscales referred to as Active Grief, Difficulty Coping and Despair (Toedter, Lasker, & Alhadeff, 1988;Toedter, Lasker, & Janssen, 2001). The Active Grief subscale contains items that reflect anguish over the death of a baby, such as, "I feel empty inside."…”
Section: Perinatal Grief Scale-33mentioning
confidence: 99%